The genus Pseudexechia Tuomikoski re-characterized, with a review of European species (Diptera: Mycetophilidae) - Kjærandsen, Jostein (Zootaxa, 2009)
The genus Pseudexechia Tuomikoski is re-characterized and described, including a thorough morphological study of the male and female terminalia, providing homology assessment of the various parts and substructures. The 25 currently known species of Pseudexechia are tentatively grouped into four species groups that are characterized mainly by structures of the male terminalia: the canalicula group (Holarctic), the longistylus group (Afrotropical) the trisignata group (Holarctic and Oriental), and the trivittata group (Holarctic and Oriental). The ten European species of Pseudexechia are then revised, of which one, Pseudexechia tuomikoskii sp. n., is described as new to science. All males and nine associated females are keyed, measured, described and illustrated. A principal component analysis of 59 morphometric measurements failed to give a clear separation of the different species and species groups. Except for overall size and some diffuse differences in flagellomere and tarsus lengths the present study also failed to reveal morphometric characters that are clearly taxonomically informative, and species identity must rest primarily on structural differences in the terminalia with aid of coloration patterns. Given as ratios, however, some measurements, like the wing vein R 4+5 bending index and the length to width ratio of clypeus, appear to be informative at species group level.